2019
DOI: 10.1002/ps.5674
|View full text |Cite
|
Sign up to set email alerts
|

A rapid insect species identification system using mini‐barcode pyrosequencing

Abstract: BACKGROUND Rapid and accurate species identification is not only important for biodiversity studies and pest quarantine and management, but in some cases may also influence the results of international trade negotiations. In this study, we developed a rapid species identification system for insects. RESULTS A universal DNA mini‐barcode primer pair was designed to target ∼ 120 bp of the mitochondrial 16S rDNA gene. This primer set can amplify the targeted region from all 300 species of 26 insect orders tested a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Traditional identification of GWF is based on morphological traits, which has several drawbacks, including reliance on expert taxonomists, time-consuming, low resolution in presence of conspecific character, presence of cryptic population, and ergonomic issues 15 17 . DNA barcoding-based species identification utilizing mitochondrial cytochrome C oxidase subunit I (mtCOI) offers rapid, reliable detection and study of genetic variation among GWF 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Traditional identification of GWF is based on morphological traits, which has several drawbacks, including reliance on expert taxonomists, time-consuming, low resolution in presence of conspecific character, presence of cryptic population, and ergonomic issues 15 17 . DNA barcoding-based species identification utilizing mitochondrial cytochrome C oxidase subunit I (mtCOI) offers rapid, reliable detection and study of genetic variation among GWF 18 .…”
Section: Introductionmentioning
confidence: 99%
“…al., 2013). Just as Hsieh et al (2020) observed that their 16S minibarcode system had resolution for species identification universality. Whereas Glover et.…”
Section: Resultsmentioning
confidence: 99%
“…Mini-barcoding by pyrosequencing has been used for species-level identification of Thrips spp. [ 208 ]. A universal primer pair for the 16S rDNA gene yields an amplicon of 120 bp.…”
Section: Pcr-based Identification Of Thrips Using Molecular Markersmentioning
confidence: 99%